Techno-Societal 2018 Proceedings of the 2nd International Conference on Advanced Technologies for Societal Applications - Volume 1 - Pawar, Prashant M.; Ronge, Babruvahan P.; Balasubramaniam, R.; Vibhute, Anup S.; Apte, Sulabha S. (Springer International Publishing : Imprint: Springer, 2020)
XIII, 1051 p. 639 illus., 540 illus. in color.